FEATURES OF FORMATION AND EXECUTION OF THE FEDERAL BUDGET IN THE MILITARY-INDUSTRIAL COMPLEX OF RUSSIA - Anzhela Z. Namitulina; Olga V. Kalashnikova (Модернизация, инновация, развитие)
Importance: The presented research topic is particularly relevant in terms of development of market relations inRussia, when indicated problems whose solution determines the positive results of reforming the economic system, an important place in which occupies the militaryindustrial complex (MIC). Among them special urgency are those that relate to the need to develop such economic relations that would ensure and guarantee the efficiency, competitiveness and sustainability of defense enterprises. In the new economic conditions, it became necessary to address the problems of financial security organizations, the military-industrial complex, the creation of an effective system to manage this process during the crisis and the need to find ways to stabilize the reproduction process inRussia. The conversion of potential military-economic opportunities in the real military power takes place on the basis of the functioning of the military economy that ensures the production and distribution of arms and military equipment. The war economy is responsible, on the one hand, the economic opportunities of the country, on the other – the nature and requirements of modern warfare. It is designed to ensure the maintenance of a constant high combat readiness of the armed forces and must be able to rapidly increase its power to the level required for the breakdown of military aggression. Problems of realization of military and economic potential are determined by the degree of use of the military and economic opportunities, as well as the effective use of financial resources.Objectives: The aim of the article is to analyze the problems of the formation and execution of defense spending. Objectives of the article: identify design characteristics of the defense component of the federal budget during the crisis of Economic Development. Methods: Methodological basis of this article are of economic and statistical methods of analysis.Results: Given that the management of the defense industry will be converted, you must use the positive experience of the international economic order to ensure the sustainability of their financial security. However, in the interests of the state and society to establish an efficient funding of defense enterprises requires a special approach for the following reasons: an effective system of financing of defense enterprises need to ensure the economic security of the country; establish a mechanism of redistribution of financial resources through economic transformation strengthens state control over the targeted use of funds; necessary, new approaches to the assessment and decision-making to improve the financial sustainability of defense enterprises. From a stable financial situation of the company and the development of DIC depends on the economy as a whole. The study gives reason to believe that at the present time inRussiaslowed down the pace of development of defense industry enterprises, has developed an unbalanced branch structure. In this regard, the study of problems related to the development of theoretical and practical tools for assessing the financial security of defense enterprises require special attention. The implementation of sound financial and economic policy, improving financial support to enterprises of the military-industrial complex of the state, identifying ways to improve the financial sustainability in transformation of the market economy is an objective necessity.Conclusions and Relevance: The practical significance of the work lies in the orientation of the provisions of the conclusions and recommendations of the work on the widespread use in improving the mechanism for defense and security, and the proposals contained in the article (to improve the planning and use of funds allocated from the state budget on defense) may be used by the legislative and executive bodies the Russian Federation, including the Ministry of Defence, in the current activity.